Dynamics of the double-well Bose-Einstein condensate coupled to a dual Markovian reservoirs system - Rajagopal, K.K. (Elsevier, 2015)
The dynamics of atomic condensate loaded in a double-well symmetric traps coupled to distinct dual reservoirs is studied. The effect of damping on the population evolution through the exposure of traps to their respective reservoir has been analysed at various temperatures. Damping in our system is induced by the fluctuation of the reservoir in agreement with the fluctuation-dissipation theorem. We found damping due to strong reservoir correlation destroy the quantum tunnelling state and macroscopic quantum self-trap state of the closed two-mode Bose-Einstein condensate states at all finite temperatures. Alternatively switching the trap's out-coupling damping rates shows significant change in the population dynamics particularly in the strongly interacting case. Dissipation coupled with strong on-site interaction in the traps exhibits even more interesting dynamics as the equilibrium temperature in system is increased. (C) 2015 Elsevier B.V. All rights reserved.